Intimate Partner Violence in lesbian, gay and bisexual couples in Metropolitan Lima - Rondan Pumachagua, Lu-Bell (2022)
The objective of this research was to analyze the perceptions of Intimate Partner Violence (IPV) in lesbian, gay and bisexual (LGB) couples in metropolitan Lima. A qualitative study was carried out, with a reflexive thematic analysis design, in which 17 LGB people who have had at least one homosexual relationship in the last year were interviewed. The analysis was carried out with the support of ATLAS.ti 22 software. The results show, on the one hand, the emotional insecurity expressed in the fears generated by jealousy that lead to situations of distrust and control behaviors, producing feelings of loneliness in the victim. In parallel to the above, this insecurity also generates dependence on the partner, which can lead to situations of violence. The other perception surrounding this violence is the justification of violence, which includes minimizing and negationist arguments of VIP, which end up normalizing it. It is concluded that the perceptions found affirm the non-specific predictors of IPV and incorporate new causal elements, such as the minimizing and negationist arguments of IPV.